Sustainable alternative livelihood for sand miners in Malang Regency, East Java, Indonesia: application of the PROMETHEE method - Suhartini, S; Prasetyo, Hendro; Gutama, Wisynu Ari; Maulana, Muhammad Fajar; Jihad, Baroroh Nur; Lasitya, Daffa Sandi; Khusni, Ahmad (Brawijaya University, 2023)
Sand mining activities on agricultural land and rivers in Bambang Village, Wajak District, Malang Regency, have been ongoing for a long time. The sand mining activities on private agricultural lands, besides being illegal, also damage the land and the environment. In addition, these sand mining activities are also unsustainable. This study aimed to analyze and formulate sustainable alternative livelihoods of sand miners on agricultural lands in Bambang Village, Wajak District, Malang Regency, based on local resources. The study method was carried out using a combination of case studies and survey methods, accompanied by in-depth interviews and field observation. The in-depth interviews were conducted by interviewing 60 respondents for key informants from miners, farmers, many stakeholders, and experts that were selected purposively. The data obtained were analyzed using a multi-criteria analysis (MCA), namely PROMETHEE (Preference Ranking Organization Methods for Enrichment Evaluation) program to formulate sustainable alternative livelihoods. The results showed that the best alternative sustainable livelihood at this location is agriculture. The second best alternative sustainable livelihood is ecotourism, the third is animal husbandry, and the fourth is informal sectors based on local resources. The government should support the development of agriculture, ecotourism, animal husbandry, and the informal sectors in the village.